2017
DOI: 10.3332/ecancer.2017.711
|View full text |Cite
|
Sign up to set email alerts
|

The presence of primary circulating prostate cells is associated with upgrading and upstaging in patients eligible for active surveillance

Abstract: Active surveillance (AS) is a considered treatment option for men with low or very low-risk prostate cancer. However, on repeat biopsy some 25% were upgraded and recommended for active treatment. We compare the presence or absence of primary circulating prostate cells (CPCs) with the clinical pathological findings after radical prostatectomy in men fulfilling the criteria for active surveillance and the risk of reclassification for active observation (AO).Methods and patientsA single centre observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…They also indicated that NLR was cheaper than the other tests and the applicability rate was higher . Murray et al investigated the circulating prostate cells (CPC) to predict upgrading and upstaging in prostate cancer. CPC positive patients had higher PSA, bioptic Gleason score pathology, and higher GU (%44.4) rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also indicated that NLR was cheaper than the other tests and the applicability rate was higher . Murray et al investigated the circulating prostate cells (CPC) to predict upgrading and upstaging in prostate cancer. CPC positive patients had higher PSA, bioptic Gleason score pathology, and higher GU (%44.4) rates.…”
Section: Discussionmentioning
confidence: 99%
“…CPC positive patients had higher PSA, bioptic Gleason score pathology, and higher GU (%44.4) rates. The authors noted that the CPC test may be useful in patients who are considered AS because the rate of upgrading and upstaging may be higher in CPC‐positive patients . Prospective randomized controlled trials may be designed on how these tests can be adapted to the follow‐up protocols of AS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Additionally, it was reported that the number of cancer-propagating cells found in prostate cancer (CPCs) correlated with GSU. [30] In order to provide patients with a safe and effective treatment plan, it would be ideal to acquire all final histopathological information. However, since the common choices in the current management of prostate cancer include options such as active surveillance and RT, current data will not be enough to overcome the problem of GSU.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the concordance between the Gleason report on biopsy and the surgical specimen is greater [ 28 ] in terms of prognosis, there were no differences between the old Gleason 6 score and the new Gleason 3 + 4 score. In addition, comparisons between the historical and new results could be invalid [ 29 31 ]. For this reason, our study has kept the old Gleason grading system.…”
Section: Discussionmentioning
confidence: 99%